The Connection Between Trauma, Pathological Personality, and Defense Mechanism in Lord of The Mysteries - Badiuzdzakwan, Ahza Naufal (Journal of Language and Literature, 2024)
The psychological problems that happen in society are growing day by day. Trauma is a common thing that can happen to somebody, and with trauma, there are also ways to handle it called defense mechanisms. From the defense mechanism, a pathological personality emerges. A person who has a pathological personality will use a defense mechanism to protect his psychological state. The connection between trauma, defense mechanisms, and pathological personality traits has become a prevalent topic of discussion. This scenario can also be found in the Lord of the Mysteries web novel where Klein Moretti as the main character experienced psychological issue in the new world. The qualitative descriptive method was used to objectively analyze the material, targeting the trauma from the main character, his defense mechanism to overcome it, and the pathological personality that emerged based on his trauma. Thus, the research aims to investigate the connection between Klein’s trauma and his pathological personality and to elaborate on what kind of defense mechanism Klein employs to overcome his trauma. Using the phenomenology approach, the researcher can collect the data based on the phenomena that happen to the main character. The researcher also does close reading while using Freudian psychoanalysis in defense mechanisms. The researcher found that trauma can create a defense mechanism due to the fact that the main character needs something to defend himself from the stress and anxiety caused by the trauma. From that trauma, pathological personality was also used by the main character to employ the defense mechanism. The researcher concludes that Klein’s defense mechanism and pathological personality are the result of his trauma.